Community Participation in Developing Educational Quality for Primary School in PakOu District Luang Prabang - Bounkeomany, Hong-Am Nart; Vathanavong, Thongthiane; Khotsaigno, Saiphone; Bounkeomany, Paphaichit (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates community involvement in enhancing the quality of primary education in Pak Ou District, Luang Prabang Province. The research objectives are: 1) to investigate the level of community participation in educational development in Pakou District, Luang Prabang Province, and 2) to compare the differences in the level of community participation in educational development in Pakou District, Luang Prabang Province. The sample comprises 106 participants, divided into three groups: primary school administrators, teachers, and community representatives. The research employed a questionnaire, consisting of open-ended and 5-point Likert scale items, as the primary data collection tool. The statistical analyses included mean ( ), standard deviation (S.D.), and One-Way ANOVA tests. The results were as follows: 1) The overall level of community participation in primary education quality development in Pak Ou District is high ( = 3.65, S.D. = 1.04). 2) The comparison of differences in the level of community participation in educational development in Pakou District, Luang Prabang Province, revealed that Different types of satisfaction have different levels of involvement, with a Sig value less than α = 0.05, indicating consistency with the hypothesized assumptions. Different levels of education have different levels of involvement, with a Sig value less than α = 0.05, indicating consistency with the hypothesized assumptions. Different levels of satisfaction have different levels of participation in some cases and not in others. Different levels of education have different levels of involvement in some cases and not in others, and different levels of satisfaction have different levels of participation, with a Sig value greater than α = 0.05, indicating inconsistency with the hypothesized assumptions.